Epistemological Parallels and Divergences: A Comparative Analysis of Legal Maxims and Fiqhiyyah Rules and Their Implications for Contemporary Jurisprudence - Erawati, Raden Rara Rita; Nurhayani, Neng Yani; Adillah, Erika Rishan (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the similarities and differences between legal maxims in the Western legal tradition and Islamic legal maxims from a comparative epistemological perspective. Using a qualitative literature study approach, the study explores the conceptual structure, sources, hierarchy, and theological, sociological, and juridical dimensions of both legal maxim systems. The results show that both serve as guidelines for legal reasoning and decision-making, providing a normative framework that guides consistency, fairness, and flexibility in legal practice. However, there are fundamental differences in their legitimacy and scope of application. Islamic maxims have a strong theological foundation, derived from the Qur'an, hadith, ijtihad, and scholarly consensus, and are structured in a systematic hierarchy from universal principles to applicable rules. These maxims also integrate vertical (human relations with God) and horizontal (human relations among humans) dimensions, thus creating a holistic and welfare-oriented legal approach. In contrast, legal maxims develop through jurisprudential practice and precedent, are more flexible, pragmatic, and focus on legal certainty and procedural justice in social interactions. This comparative analysis not only demonstrates functional similarities and normative objectives but also highlights the potential for epistemological integration between the two legal traditions. The research findings provide an important contribution to contemporary legal development, particularly in countries with pluralistic legal systems like Indonesia, where dialogue between Islamic and Western law can enrich national legal methodology, support the formation of adaptive, contextual, and equitable regulations, and equip practitioners and academics with more comprehensive insights.